in the diagnosis of acute appendicitis in patients referred to Shahid Faghihi Hospital, Shiraz - Maryam Soltani; Ahmad Abdollahi; Majid Akrami; Jafar Hassanzadeh (Shiraz University of Medical Sciences, 2018)
Introduction: Acute appendicitis is the major cause of abdominal pain which indicates urgent surgery. Commonly, it is diagnosed through clinical signs and symptoms and blood test. This study aimed to assess the  accuracy of acute appendicitis diagnosis through signs and symptoms, Alvarado score system, and ultrasonography method. Methods: This was a cross-sectional study. Medical profiles of 696 patients with abdominal pain suspected of acute appendicitis referred to Shahid Faghihi hospital were reviewed from June to October 2016. A checklist was used for data collection. The gold standard for diagnosis of acute appendicitis was patient's pathology report. For signs and symptoms, Alvarado score system and ultrasonography method sensitivity, specificity, positive and negative predictive value, and the Youden's index were calculated based on true positive and true negative values. Results: Among 696 patients suspected of acute appendicitis, 371 (53.3%) were men and 325 (46.7%) women. The mean age for women and men was 30.14+11.49  and 30.53+11.61 years, respectively. Sensitivity and specificity for ultrasonography and Alvarado score system were 68.1% and 78.9%, 76.1%, and 59.9%, respectively. The areas under roc curve and the Youden's index for ultrasonography and Alvarado score system were 0.73, 0.47, and 0.71, 0.55, respectively.  Conclusion: The results showed that ultrasonography and Alvarado score system were effective pre-surgical diagnostic tests for patients suspected of acute appendicitis.